Design and optimization of innovative food processing techniques - Barba, Francisco (Francisco J.) (Academic Press, 2021)
Design and Optimization of Innovative Food Processing Techniques Assisted by Ultrasound: Developing Healthier and Sustainable Food Products is a useful tool in understanding the innovative applications derived from the use of ultrasound technology. The book is a starting point for product development, covering technological, physicochemical and nutritional perspectives, as well as the reduction of food toxics and contaminants. Divided into three parts, sections cover ultrasound usage in obtaining functional foods, extracting bioactive compounds, the improvement of food quality, ultrasound use for the development of novel applications, and more. As the definitive resource in new innovative ultrasound-based emerging processes, this book is a necessity for food scientists and technologists, nutrition researchers, and those working in the food manufacturing industry.